THE EFFECT OF 30% RUBRA VARIETY OF ALPINIA GALANGA RHIZOME EXTRACT CREAM AS A TREATMENT TO ORAL CANDIDOSIS - Dyah Juniar Hynawatty (Faculty of Dentistry, Universitas Indonesia, 2015)
The rubra variety of Alpinia galanga rhizome extract were compatible to the fibroblast tissue, non toxic, and potent in inhibiting Candida albicans growth. The purpose of this study was to find out the effect of the rubra variety of Alpinia galangal rhizome extract as a treatment to oral candidosis. The patients involved in this study were 20 diabetic patients, men and women. There were sixteen patients showed white patches of flecks on the tongue surface. After clinical examination, a direct smear was made and there were mass of candida hyphae on Periodoc Acid Schiff staining. For patient comfort, the extract of Alpinia galangal 30% was prepared as a cream in a tube. The cream was used topically on the flack, 4-5 times daily for 14 days. In case of the flecks persisted, the treatment was continued to 21 days. Mc Nemar test showed a significant difference between the group before and after treatment (p<0,05). It was concluded that 30% rubra variety of Alpinia galanga rhizome extract could be used as an alternative treatment for oral candidosis.